2000
DOI: 10.1063/1.373462
|View full text |Cite
|
Sign up to set email alerts
|

The refractive index of AlxGa1−xAs below the band gap: Accurate determination and empirical modeling

Abstract: The refractive indices of AlxGa1−xAs epitaxial layers (0.176⩽x⩽1) are accurately determined below the band gap to wavelengths, λ<3 μm. The layers are grown on GaAs substrates by molecular beam epitaxy metal organic and chemical vapor deposition with thicknesses ranging from 4 to 10 μm. They form improper waveguide structures with the GaAs substrate. The measurements are based on the excitation of the improper waveguide modes with grating couplers at 23 °C. The refractive indices of the layers are derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
165
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(174 citation statements)
references
References 37 publications
8
165
0
1
Order By: Relevance
“…For GaAs at 300 K, the de Broglie wavelength of the conduction electrons is , = 2.ℏ /201 2 ⁄ ≈ 30 nm, where 2 = 300 K, ℏ the Planck constant, 1 the Boltzmann constant, 0 = 0.0670 the electron effective mass, and 0 is the free-electron mass. When the dot size is smaller than , , quantum confinement effects become relevant, giving rise to a discrete energy spectrum and an increasing S3 inter-band separation, 8 , for a decreasing dot size, as shown in Figure S1B, which also displays the results of ab initio calculations 4,5 .…”
Section: S1 Optical Absorption In Qdsmentioning
confidence: 81%
See 2 more Smart Citations
“…For GaAs at 300 K, the de Broglie wavelength of the conduction electrons is , = 2.ℏ /201 2 ⁄ ≈ 30 nm, where 2 = 300 K, ℏ the Planck constant, 1 the Boltzmann constant, 0 = 0.0670 the electron effective mass, and 0 is the free-electron mass. When the dot size is smaller than , , quantum confinement effects become relevant, giving rise to a discrete energy spectrum and an increasing S3 inter-band separation, 8 , for a decreasing dot size, as shown in Figure S1B, which also displays the results of ab initio calculations 4,5 .…”
Section: S1 Optical Absorption In Qdsmentioning
confidence: 81%
“…The FDTD simulations predict that for dot dimensions smaller than the photon wavelength, the fraction, , of laser intensity absorbed by the dot decreases for a decreasing size. On the other hand, for a decreasing dot size, the energy gap, 8 , gets closer to the photon energy, approaching the condition for a resonant electronic excitation, which is described by the relevant increase of the factor ! " #$ !…”
Section: S1 Optical Absorption In Qdsmentioning
confidence: 93%
See 1 more Smart Citation
“…The heat−transfer coefficient for the bottom heat−sink surface has been assumed as equal to 50 Wm -2 K -1 . Refractive indices have been reported by Gehrsitz et al [33], Gini and Melchior [34], Chandra et al [35], and Henry et al [36], Lee and Lee [37] or found in www.virginiasemi.com. Temperature−dependent absorption coefficients have been given in [38][39][40][41][42][43][44][45].…”
Section: Model Parametersmentioning
confidence: 99%
“…1(a), the incident light was a plane wave with a wave vector, k, parallel to the cylinder axis and the electric field, E, polarized along the x-axis. For the dispersion of the refractive index of Al 0.18 Ga 0.82 As we used the analytical model proposed in [18] which was derived from comparison with measurements. The scattering efficiency (defined as Q sca = C sca /πr 2 where C sca is the scattering cross-section and r is the cylinder radius) calculated for a cylinder suspended in air with radius r = 225 nm and height h = 400 nm is shown in Fig.…”
Section: Design Of Algaas Nanoantennasmentioning
confidence: 99%